Fusible flux for fillet submerged arc welding
Patent Information
- Application Number
- JP2021111049
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-22
- Filing Date
- 2021-07-02
- Publication Date
- 2025-02-13
- Estimated Expiration
- 2041-07-02
Smart Images

Figure 0007629365000008 
Figure 0007629365000009 
Figure 0007629365000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a molten flux for fillet submerged arc welding, and in particular to a molten flux for fillet submerged arc welding which, when used for fillet welding with large heat input on columns and beams made of built H-section steel that is often used in buildings, bridges, and the like, can produce a stable arc, have good bead shape and slag removability, and produce a weld metal with good toughness. [Background technology]
[0002] In recent years, there has been a trend toward thicker steel plates for use in steel structures such as buildings and bridges, and submerged arc welding with a large heat input is being used to weld efficiently. Also, to ensure the safety of steel structures, learning from examples of destruction caused by earthquakes and other events, stable weld metal properties are required even when welding with a large heat input.
[0003] Welded joints formed by fillet submerged arc welding are required to have a good penetration depth, leg length, smoothness of the bead shape, and good compatibility between the weld metal and the base material. In recent years, there has been a trend for fillet weld metal to have good mechanical properties due to the damage to steel structures caused by earthquake disasters and their increasing size.
[0004] Conventionally, when a certain mechanical performance is required for the weld metal formed by fillet submerged arc welding, a sintered flux to which alloys can be added has been used, as disclosed in, for example, Patent Document 1. However, since the sintered flux has a high melting point, when welding is performed at a relatively high speed, the bead shape is poor, such as bead waveform and poor conformity of the bead toe, and the welding efficiency cannot be improved.
[0005] On the other hand, molten fluxes for fillet submerged arc welding are disclosed, for example, in Patent Document 2 and Patent Document 3. The techniques disclosed in Patent Document 2 and Patent Document 3 are intended to improve slag removability and bead appearance and shape during high-speed fillet welding, but have a problem in that the toughness of the weld metal cannot be obtained when fillet welding is performed with a large current.
[0006] Also, Patent Document 4 discloses a fusible flux for fillet submerged arc welding that can provide good toughness to the weld metal of the fillet weld. However, the fusible flux described in Patent Document 4 contains SiO 2 There is little Al 2 O 3 and TiO 2 Therefore, when fillet welding is performed with a large heat input, the bead shape is convex, and slag adhesion occurs, resulting in poor slag removability. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2010-125508 A [Patent Document 2] Japanese Patent Application Publication No. 53-133543 [Patent Document 3] Japanese Patent Publication No. 154791 / 1983 [Patent Document 4] Japanese Patent Publication No. 183996 / 1983 Summary of the Invention [Problem to be solved by the invention]
[0008] Therefore, the present disclosure has been devised in consideration of the above-mentioned problems, and has an object to provide a molten flux for fillet submerged arc welding, which can provide a stable arc, good bead shape and slag removability, and a weld metal with good toughness when performing fillet submerged arc welding. [Means for solving the problem]
[0009] The gist of the present disclosure for solving the above problems is as follows. <1> Mass % of the total flux mass SiO 2 : 35~45%, MnO: 18-28%, Al 2 O 3 :6~20%, MgO: 11-16%, TiO 2 :2~6%, FeO: 0.5-4%, CaF 2 :5-9%, and Na 2 O and K 2 Total of one or two types of O: 0.5 to 1.0% The remainder of the flux component is impurities, The basicity A calculated from the following formula (1) is 0.50 to 1.00, The bulk density of the flux is 0.8 to 1.3 g / cm 3 That is, Fusible flux for fillet submerged arc welding. A = ([CaF 2 ]+[MgO]+0.5([MnO]+[FeO])) / ([SiO 2 ]+0.5([Al 2 O 3 ]+[TiO 2 ]))...Equation (1) Here, [ ] indicates the mass % of each component relative to the total mass of the flux. <2> The flux particles have a particle size in the range of more than 0.3 mm to 1.4 mm in mass % relative to the total mass of the flux. <1> 2. A molten flux for fillet submerged arc welding according to claim 1. <3> In place of a part of the flux components, in mass% relative to the total mass of the flux, Bi 2 O 3 Contains 0.05% or less <1> or <2> 2. A molten flux for fillet submerged arc welding according to claim 1. <4> In place of a part of the flux components, in mass% relative to the total mass of the flux, B 2 O 3 Contains 1.5% or less <1> ~ <3> 10. The fillet submerged arc welding molten flux according to claim 9, <5> In place of a part of the flux components, in mass% relative to the total mass of the flux, Contains one or both of CaO: 5.0% or less and BaO: 5.0% or less <1> ~ <4> 10. The fillet submerged arc welding molten flux according to claim 9, Effect of the Invention
[0010] According to the present disclosure, there is provided a molten flux for fillet submerged arc welding which, when performing fillet submerged arc welding, enables a stable arc to be obtained, resulting in a weld metal with good bead shape, good slag removability, and good toughness. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1(a) is a schematic diagram showing the shape of a welded test plate used in an embodiment of the present disclosure with groove processing, and FIG. 1(b) is a schematic diagram showing the shape of a welded test plate used in an embodiment of the present disclosure without groove processing. [Diagram 2] FIG. 2 is a schematic diagram showing the locations where Charpy impact test specimens of the examples of the present disclosure were taken. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present inventors conducted a detailed study on the component composition of a molten flux for fillet submerged arc welding, which provides a stable arc, good slag removability and bead shape, and good toughness of the weld metal in large heat input submerged arc welding of H-shaped steel with and without a groove.
[0013] As a result, the arc stability is 2 O and K 2The total amount of one or two types of O is appropriate, and the slag removability is improved by using MnO, TiO 2 , FeO and CaF 2 By using an appropriate amount of SiO 2 , MnO, Al 2 O 3 , MgO, TiO 2 , FeO, CaF 2 , and Na 2 O and K 2 It has been found that the bulk density of the flux can be improved by controlling the total amount of one or two of the O species to an appropriate amount.
[0014] In addition, in order to improve the toughness of the weld metal of the fillet welds produced by high heat input welding, SiO 2 , MgO and TiO 2 It has been found that this can be achieved by optimizing the amount of the flux and by optimizing the basicity and bulk density of the flux.
[0015] In addition, Bi is used in place of some of the above ingredients. 2 O 3 By adding an appropriate amount of B, the slag removability can be improved. 2 O 3 It has been found that the toughness of the weld metal of a fillet weld by large heat input welding can be further improved by adding appropriate amounts of CaO and BaO.
[0016] Hereinafter, the components (flux components) of the molten flux for fillet submerged arc welding of the present disclosure (sometimes referred to as "molten flux" or simply "flux" in the present disclosure) and the reasons for limiting the composition, etc. will be described. The content of each component composition will be expressed as mass% relative to the total mass of the flux, and the description of mass% will be expressed simply as %. Furthermore, when the content is limited to an upper limit value such as "~% or less" without specifying a lower limit value, this means that the component is not included, i.e., the content may be 0%, or the component may be included in the range of more than 0% to the upper limit value.
[0017] [SiO 2 :35~45%] SiO made from silica sand, wollastonite, etc. 2 SiO adjusts the viscosity of the molten slag to improve the bead shape. 2 If the SiO content is less than 35%, the viscosity of the molten slag is insufficient, causing the bead to meander or undercut, resulting in a poor bead shape. 2 If SiO exceeds 45%, the oxygen content of the weld metal increases and the toughness decreases. 2 should be between 35 and 45%.
[0018] [MnO: 18-28%] MnO, which is made from manganese oxide, roasted manganese, etc., is an effective component for adjusting the viscosity and slag removability of the molten slag. However, if the MnO content is less than 18%, the viscosity of the molten slag increases, and the slag burns to the bead, resulting in poor slag removability. On the other hand, if the MnO content exceeds 28%, the viscosity of the molten slag decreases, and overlap and undercut occur. Therefore, the MnO content is set to 18-28%.
[0019] [Al 2 O 3 :6~20%] Al made from alumina etc. 2 O 3 Al is an effective component for adjusting the viscosity of molten slag. 2 O 3 If the content of Al is less than 6%, the viscosity of the molten slag will be low and undercuts will easily occur. 2 O 3 If Al exceeds 20%, the viscosity of the molten slag becomes too high and the bead becomes convex. 2 O 3 should be between 6 and 20%.
[0020] [MgO: 11-16%] MgO, which is made from magnesia clinker and other raw materials, adjusts the viscosity of the molten slag to improve the bead shape. MgO also reduces the amount of oxygen in the weld metal, improving toughness. If the MgO content is less than 11%, the viscosity of the molten slag will be insufficient, causing the bead to meander and undercut. If the MgO content is less than 11%, the oxygen content of the weld metal will be too high, reducing toughness. On the other hand, if the MgO content exceeds 16%, the bead width will be narrowed and hot cracking will be more likely to occur. Therefore, the MgO content is set to 11-16%.
[0021] [TiO 2 :2~6%] TiO made from raw materials such as rutile and titanium oxide 2 is effective in obtaining smoothness on the bead surface. 2 TiO acts as a nucleus for acicular ferrite in the weld metal, promoting the refinement of the weld metal structure and is an extremely effective component in improving toughness. 2 If the amount of TiO is less than 2%, the spread of the bead toe becomes discontinuous. 2 If the content of TiO is less than 2%, the toughness of the weld metal decreases. 2 If TiO exceeds 6%, the slag will burn and the slag removal will be poor. 2 is between 2 and 6%.
[0022] [FeO: 0.5-4%] FeO, which is derived from mill scale and other raw materials, adjusts the viscosity and melting point of the molten slag, improves the conformity of the bead toe, and improves the bead shape. If FeO is less than 0.5%, the conformity of the bead toe is poor and the bead shape is poor. On the other hand, if FeO exceeds 4%, the slag will stick and the slag removability will be poor. Therefore, FeO is set to 0.5 to 4%.
[0023] [CaF 2 :5~9%] CaF made from fluorite etc. 2 CaF has the effect of adjusting the fluidity of the molten slag and improving the slag removability. 2 If the content is less than 5%, the slag will stick to the bead and the slag will not be easily removable.2 If CaF exceeds 9%, the fluidity of the slag increases, overlap and undercut occur, and the gas content increases, causing pockmarks. 2 If CaF exceeds 9%, the bead becomes convex during high current and high speed fillet welding, making it more susceptible to hot cracking. 2 is set at 5-9%.
[0024] [Na 2 O and K 2 Total of one or two types of O: 0.5-1.0% Na made from sodium carbonate and potassium carbonate, etc. 2 O and K 2 O is an effective component for improving the arc stability, making the bead wavy and improving the bead appearance. 2 O and K 2 If the total of one or both of the O elements is less than 0.5%, the arc becomes unstable, the bead becomes rough, and the appearance becomes poor. 2 O and K 2 If the total of one or both types of O exceeds 1.0%, undercutting is likely to occur. 2 O and K 2 The total of type 1 or type 2 O should be 0.5 to 1.0%.
[0025] [Basicity A: 0.50~1.00] The basicity A of each of the components described above, calculated from the following formula (1), adjusts the viscosity of the molten slag. It also reduces the amount of oxygen in the weld metal to improve toughness. If the basicity A is less than 0.50, the amount of oxygen in the weld metal increases, resulting in low toughness. On the other hand, if the basicity A exceeds 1.00, the viscosity of the slag increases, resulting in poor slag removability. Therefore, the basicity A calculated from the following formula (1) is set to 0.50 to 1.00. A = ([CaF 2 ]+[MgO]+0.5([MnO]+[FeO])) / ([SiO 2 ]+0.5([Al 2 O 3 ]+[TiO 2 ]))...Equation (1) Here, [ ] indicates the mass % of each component relative to the total mass of the flux.
[0026] [Bulk density of flux: 0.8~1.3g / cm 3 ] The bulk density of the flux measured according to JIS K-6720 affects the shielding of the molten pool from the atmosphere during welding and the spread of the weld bead. 3 If the flux has a bulk density of less than 1.3 g / cm3, the shielding during welding is insufficient, the nitrogen and oxygen in the weld metal increase, and the toughness decreases. 3 If the flux density exceeds 0.8 to 1.3 g / cm, the bead does not spread and undercut occurs. 3 Let us assume that.
[0027] The bulk density of the flux can be adjusted by a manufacturing method in which the molten flux is cooled in hot water and foamed by slowing down the cooling rate during the flux manufacturing process, or by cooling the molten flux in a water jet to form a flux containing a mixture of needle-shaped, antler-shaped, spherical, and scale-shaped particles.
[0028] The bulk density of the flux is measured in accordance with JIS K6720. Bulk density (g / cm 3 ) = (mass of the receiver containing the sample (g) - mass of the receiver (g)) / internal volume of the receiver (cm 3 )
[0029] In addition, as a method for adjusting the particle size of the flux, for example, a method of directly applying a jet of water to the molten flux (melt) can be mentioned. The particle size of the flux can be adjusted by controlling the water pressure, the amount of water, and the amount of the molten flux to granulate it and sieve it.
[0030] [Bi 2 O 3 :0.05% or less] Bi made from bismuth oxide etc. 2 O3 However, Bi has the effect of improving slag removability. 2 O 3 If Bi exceeds 0.05%, the toughness of the weld metal deteriorates. 2 O 3 The content of Bi is 0.05% or less. 2 O 3 Although the effect of improving slag removability can be obtained by adding a small amount, in order to obtain this effect, it is preferable to add 0.001% or more.
[0031] The balance of the molten flux for fillet submerged arc welding of the present disclosure is impurities contained in the raw materials in trace amounts, such as CaO, BaO, P, and S, and the like, and the total content of these may be 3% or less. In addition, the molten flux for fillet submerged arc welding disclosed herein contains B instead of a part of the above-mentioned flux components. 2 O 3 , CaO, and / or BaO may each be contained in a predetermined amount.
[0032] [B 2 O 3 :1.5% or less] B made from boron oxide etc. 2 O 3 has the effect of improving the toughness of the weld metal. 2 O 3 If B exceeds 1.5%, the toughness of the weld metal deteriorates. 2 O 3 If it contains B, it should be 1.5% or less. 2 O 3 The effect of improving the toughness of the weld metal can be obtained, but in order to obtain this effect, the content is preferably 0.01% or more.
[0033] [CaO:5.0% or less] CaO, which is made from calcium oxide and other raw materials, has the effect of improving the toughness of the weld metal. However, if CaO exceeds 5.0%, the bead becomes convex. Therefore, if CaO is contained, it should be 5.0% or less. CaO has the effect of improving the toughness of the weld metal, but to obtain this effect, it is preferable to make it 0.01% or more.
[0034] [BaO:5.0% or less] BaO, which is made from barium oxide and the like, has the effect of improving the toughness of the weld metal. However, if BaO exceeds 5.0%, the bead becomes convex. Therefore, if BaO is contained, it should be 5.0% or less. Note that BaO has the effect of improving the toughness of the weld metal, but to obtain this effect, it is preferable to make it 0.01% or more.
[0035] The particle size of the flux is not particularly limited, but it is preferable that 90% or more of the flux particles have a particle size in the range of more than 0.3 mm to 1.4 mm. The particle size of the flux is measured by the method described later as an example. EXAMPLES
[0036] The effects of the molten flux according to the present disclosure will be specifically described below using examples.
[0037] <Example 1> Molten fluxes having the respective component compositions, basicity A, and bulk density shown in Table 1 were prepared, and welding tests were performed under the two-electrode submerged arc welding conditions shown in Table 2 using a JIS Z3351 YS-S6 solid wire with a wire diameter of 4.8 mm shown in Table 4 and JIS G3136 SN490B steel plates with thicknesses of 25 mm and 16 mm shown in Table 3. For the groove shape, as shown in Fig. 1(a), the 25 mm thick steel plate was assembled to the flange steel plate 2 in a T-shape with a 60° double-sided groove and a root face of 9 mm on the web steel plate 1, and double-sided welding was performed by flat-position fillet submerged arc welding using all the prototype fluxes to produce test specimen 10. For the 16 mm thick steel plate, as shown in Fig. 1(b), the web steel plate 1 and the flange steel plate 2 were assembled to a T-shape without a groove, and double-sided welding was performed by flat-position fillet submerged arc welding in combination with some of the prototype fluxes to produce test specimen 11.
[0038] The particle size of the flux was adjusted to be on a 0.3 mm sieve and below a 1.4 mm sieve.
[0039] The balance in the flux component composition in Table 1 is CaO, BaO, P, S, etc., which are mixed in as impurities from the raw materials. The underlines in the table indicate that they are outside the scope of the present disclosure.
[0040] [Table 1]
[0041] [Table 2]
[0042] [Table 3]
[0043] [Table 4]
[0044] The welding workability was evaluated by investigating arc stability, bead shape (bead meandering, undercut, overlap, bead spread, etc.), slag removability, and the presence or absence of hot cracks.
[0045] Arc stability was considered good if the welding voltage fluctuation during welding was within ±5V.
[0046] The bead shape was determined by measuring the bead width at 10 points on the healthy part of the weld bead. If the difference between the minimum and maximum values was within 8 mm and there were no weld defects (bead meandering, undercut, overlap, etc.), the weld was deemed good.
[0047] As the slag peels off naturally after welding, the slag was removed with a brush, and the area of the remaining slag that could be visually confirmed was estimated, with a slag removal rate of 98% or more being considered good. Also, the area of the remaining slag that could be visually confirmed within a 30 cm range of the sound bead was estimated, and a slag removal rate of 100% was considered extremely good.
[0048] The mechanical properties were evaluated by taking a Charpy impact test piece 3 (JIS Z2202 No. 4) from the center of the fillet weld metal 20 as shown in Figure 2 from a welded test specimen 12 consisting of a 25 mm thick web steel plate 1 and a flange steel plate 2. The Charpy impact test was performed three times at a test temperature of 0°C, and an average absorbed energy of 50 J or more was considered good. The results are summarized in Table 5. Note that in Table 5, for the test specimen shown in Figure 1, the 25 mm thick plate with groove preparation shown in Figure 1(a) is indicated as "a," and the 16 mm thick plate with no groove preparation shown in Figure 1(b) is indicated as "b."
[0049] [Table 5]
[0050] In Tables 1 and 5, the flux symbols F1 to F10 are examples of the present invention, and the flux symbols F11 to F22 are comparative examples. The flux symbols F1 to F10, which are examples of the present invention, are SiO 2 , MnO, Al 2 O 3 , MgO, TiO 2 , FeO, CaF 2 , Na 2 O and K 2The total amount of one or two of O is appropriate, and the basicity A and bulk density of the flux are appropriate. Therefore, in flat fillet welding with a plate thickness of 25 mm with groove preparation and with a plate thickness of 16 mm without groove preparation, the arc is stable, and there is no bead meandering, undercut, overlap, or convex bead, and the bead shape is good. The slag removability is good, and no high-temperature cracking occurs. The absorbed energy of the weld metal is high, and the results are very satisfactory. 2 O 3 Fluxes F2, F3, F6, F8 and F10, which contain an appropriate amount of, had extremely good slag removability.
[0051] In the comparative examples, the flux symbol F11 is SiO 2 Since there is little gap, the bead meanders and undercuts occur both with and without groove preparation. 2 Since the amount of slag was small, slag was stuck to the surface and the slag removability was poor.
[0052] Flux symbol F12 is SiO 2 The amount of FeO was so high that the absorbed energy of the weld metal was low. Also, the amount of FeO was so low that the bead toe did not conform well and the bead shape was poor.
[0053] Flux code F13 contains a small amount of MnO, so slag sticks and the slag removal is poor. 2 O and K 2 Because the total amount of O type 1 or type 2 was low, the arc was unstable, the bead was rough and wavy, and the appearance was poor.
[0054] Flux F14 had a high MnO content, which caused overlap and undercut, and a high FeO content, which caused slag to stick and resulted in poor slag removability.
[0055] Flux symbol F15 is Al 2 O 3 Because the amount of TiO was small, undercutting occurred. 2 As a result, slag was stuck to the surface and slag removability was poor.
[0056] Flux symbol F16 is Al 2 O 3 The bead was convex because of the high basicity A. Also, the absorbed energy of the weld metal was low because of the low basicity A.
[0057] Flux code F17 has a low MgO content, so the bead meanders and undercuts occur both with and without groove preparation. Also, because of the low MgO content, the absorbed energy of the weld metal is low.
[0058] Flux F18 contained a lot of MgO, which resulted in narrow bead width and crater cracks. In addition, the bulk density of the flux was low, so the absorbed energy of the weld metal was low.
[0059] Flux code F19 is TiO 2 The bead toe was discontinuous because of the small amount of TiO 2 The absorbed energy of the weld metal was low because the basicity A was low. Furthermore, the slag removability was poor because the basicity A was high.
[0060] Flux code F20 is CaF 2 As a result, overlaps, undercuts and pockmarks occurred, and the bead became convex, causing crater cracks. 2 O 3 Therefore, the absorbed energy of the weld metal was low.
[0061] Flux symbol F21 is Na 2 O and K 2 Because the total of one or two types of O was high, undercutting occurred.
[0062] Flux code F22 has a high bulk density, so the bead width was narrow and undercut occurred both with and without groove preparation.
[0063] <Example 2> Melt type fluxes having the component compositions, basicity A, bulk density and particle sizes (mass proportion of particle sizes from 0.3 mm to 1.4 mm) shown in Table 6 were produced as prototypes. The remainder in the flux component composition in Table 6 is P, S, etc., which are mixed in as impurities from the raw materials.
[0064] The particle size of the flux was measured in accordance with "6.3 Flux Particle Size Test" in JIS Z3352:2017 Flux for Submerged Arc Welding and Electroslag Welding after grading the particles on a 0.3 mm sieve mesh to under a 1.4 mm sieve mesh. Sieves with nominal openings (300 μm and 1.4 mm) equivalent to those in JIS Z 8801-1:2019 "Test sieves - Part 1: Metal mesh sieves" were used, and the sieving time was 4 minutes. Mechanical sieving was performed according to JIS Z8815:1994 "General rules for sieving test methods," and a low-tap type sieve shaker was used as the measuring device. The flux used for the test was 200 g. In such a particle size test of flux, a flux that passes through a sieve with a nominal mesh size of 1.4 mm and does not pass through a sieve with a nominal mesh size of 300 μm is a flux with a particle size of more than 0.3 mm to 1.4 mm.
[0065] The fluxes F31 and F32 are made from the same raw materials and have the same flux components, but the particle size and bulk density were adjusted by changing the grinding conditions and sieving time when producing the flux.
[0066] [Table 6]
[0067] Except for using flux codes F31 to F38, the same procedure as in Example 1 was used to prepare test specimens 10 that were double-sided welded by flat-position fillet submerged arc welding as shown in Fig. 1(a), and the welding workability and mechanical properties were evaluated. The results are shown in Table 7.
[0068] [Table 7]
[0069] The flux symbols F31 to F38, which are examples of the present invention, are all SiO 2 , MnO, Al 2 O 3 , MgO, TiO 2 , FeO, CaF 2 , Na 2 O and K 2 The total amount of type 1 or type 2 O was appropriate, and the basicity A and bulk density of the flux were also appropriate, so in flat fillet welding with groove preparation on a plate thickness of 25 mm, the arc was stable and there was no bead meandering, undercut, overlap or convex bead, and the bead shape was good. The slag removability was also good and no high-temperature cracking occurred. The absorbed energy of the weld metal was high, and the results were extremely satisfactory.
[0070] In addition, although the flux codes F31 and F32 have the same components, the flux code F31, which has 90% or more of flux particles with a particle size in the range of more than 0.3 mm to 1.4 mm, showed better slag removability, higher absorbed energy in the weld metal, and superior toughness. Flux symbols F33 to F38 contain the above ingredients plus B 2 O 3 The flux contains at least one of the elements selected from the group consisting of CaO, BaO, and ZnO. Compared to the flux with F31, the weld metal had higher absorbed energy and better toughness. [Explanation of symbols]
[0071] 1 Web steel plate 2 Flange steel plate 3 Charpy impact test specimen 10, 11 Test specimen 12 Welded test specimen 20 Fillet weld metal
Claims
1. Mass % relative to the total mass of the flux Yes 2 :35~45%, MnO: 18-28%, <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> :6~220%、 MgO: 11-16%, TO 2 :2~6%, FeO: 0.5-4%, CaF 2 : 5 to 9%, and Na 2 O and K 2 Total of one or two types of O: 0.5 to 1.0% and the balance being 3% or less of impurities, The basicity A calculated from the following formula (1) is 0.50 to 1.00, The bulk density of the flux is 0.8 to 1.3 g / cm 3 That is, Fusible flux for fillet submerged arc welding. A = ([CaF 2 +[MgO]+0.5([MnO]+[FeO])) / ([SiO 2 +0.5([Al 2 O 3 +[TiO 2 ))... (Equation (1)) Here, the brackets [ ] indicate the mass % of each component relative to the total mass of the flux.
2. 2. The molten flux for fillet submerged arc welding according to claim 1, wherein, in terms of mass%, 90% or more of flux particles have a particle size in the range of more than 0.3 mm to 1.4 mm with respect to the total mass of the flux.
3. In place of a part of the flux components, in mass % relative to the total mass of the flux, Bi 2 O 3 3. The molten flux for fillet submerged arc welding according to claim 1, further comprising 0.05% or less of Cr.
4. In place of a part of the flux components, in mass % relative to the total mass of the flux, B 2 O 3 4. The molten flux for fillet submerged arc welding according to claim 1, further comprising 1.5% or less of Cr.
5. In place of a part of the flux components, in mass % relative to the total mass of the flux, The molten flux for fillet submerged arc welding according to any one of claims 1 to 4, containing one or both of CaO: 5.0% or less and BaO: 5.0% or less.
Citation Information
Patent Citations
Kamu
JP1976046653A
Flux for submerged arc welding
JP1978133543A
Molten flux for submerged arc welding
JP1982039092A
Fused flux for submerged arc welding
JP1984076698A
Fused flux for submerged arc welding
JP1985187495A